Indonesia Public Expenditure and Financial Accountability : Assessment Report 2017 - World Bank Group (World Bank, Jakarta, 2018)
Indonesia has experienced strong economic growth and steady poverty reduction over the past decade,but the end of the commodity boom, accompanied by slowing poverty reduction and rising inequality, has put pressure on the country's overall economic development. Indonesia's average annual growth rate was 5.6 percent in the period 2001-12, equivalent to a GDP per capita of about US 3,500 dollars. The national poverty rate was halved to 11.2 percent in the period from 1999 to 2015, largely through sustained growth and job creation. However, the decline in commodity prices and demand slowed growth to 4.8 percent in 2015 and 5.1 percent in 2016. The pace of poverty reduction also began to stagnate around this time, with a near zero decline in 2015, accompanied by rising inequality, from 30 points in 2000 to 41 points by 2014, as measured by the Gini coefficient.